UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DI DALAM KELAS MELALUI BIMBINGAN KELOMPOK DI SMA N 2 BANGKO KABUPATEN ROKAN HILIR: (Efforts to Improve Student Learning Motivation In Class through Group Counseling at SMA N 2 Bangko Rokan Hilir) - Hayati Tatoe (Perspektif Pendidikan dan Keguruan, 2017)
Students' motivation is low need to be addressed with the right approach. Model approach to behavioral counseling through group counseling services need to be done. The purpose of this study was to determine the increase in students' motivation in the classroom through group counseling. Counseling teachers do in class XB public high school 2 Bangko. This study design using Action Research (PTK) designed two cycles of the first cycle and the second cycle. The subjects were students class XB public high school Bangko, Rokan Hilir. Analysis of data using qualitative descriptive analysis Cycle I pointed out, the average class XB learning motivation is low then do the second cycle. Based on the action given that the guidance of the group in the classroom can increase the motivation of students in public high school 2 Bangko, Rokan Hilir. .